2020
DOI: 10.1029/2019pa003738
|View full text |Cite
|
Sign up to set email alerts
|

Planktic Foraminiferal Test Size and Weight Response to the Late Pliocene Environment

Abstract: Atmospheric carbon dioxide (pCO 2 atm ) is impacting the ocean and marine organisms directly via changes in carbonate chemistry and indirectly via a range of changes in physical parameters most dominantly temperature. To assess potential impacts of climate change on carbonate production in the open ocean, we measured size and weight of planktic foraminifers during the late Pliocene at pCO 2 atm concentrations comparable to today and global temperatures 2 to 3°C warmer. Size of all foraminifers was measured at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 94 publications
0
19
1
Order By: Relevance
“…However, while our chosen species for pH/CO 2 reconstruction, G. ruber, is known to be relatively susceptible to partial dissolution on the seafloor 43 , its δ 11 B signal has been observed to be robust 14,44 . Furthermore, a recent study 45 of test weight and fragmentation at ODP 999 showed that tests become better preserved during M2 ( Supplementary Fig. 7), as observed during glacial periods of the late Pleistocene 46 .…”
Section: M2 Glaciation -The Role Of Co 2 Marine Isotope Stage M2 (Amentioning
confidence: 56%
“…However, while our chosen species for pH/CO 2 reconstruction, G. ruber, is known to be relatively susceptible to partial dissolution on the seafloor 43 , its δ 11 B signal has been observed to be robust 14,44 . Furthermore, a recent study 45 of test weight and fragmentation at ODP 999 showed that tests become better preserved during M2 ( Supplementary Fig. 7), as observed during glacial periods of the late Pleistocene 46 .…”
Section: M2 Glaciation -The Role Of Co 2 Marine Isotope Stage M2 (Amentioning
confidence: 56%
“…Both PF and L. helicina are sensitive to the carbonate chemistry in their environment and the extent of their calcification is commonly used as an indicator for OA [33][34][35][36][37][38][39][40]. Furthermore, due to their long sedimentary record PF shell density has been used for paleoceanographic studies of OA and atmospheric CO 2 [41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other aspects of the growth habitat, including temperature, salinity, and food availability, may drive changes in foraminiferal growth and calcification, and thus influence SNW (Beer et al, 2010b;Bijma et al, 1990;Broecker & Clark, 2001;de Villiers, 2004;Pak et al, 2018;Todd et al, 2020;Weinkauf et al, 2016). In some paleoceanographic records, dissolution proxies such as fragmentation counts and external smoothing of shell features show a decoupling between dissolution and SNW (Davis et al, 2016;Pak et al, 2018;Todd et al, 2020 counts as an independent measure of dissolution and found that variation in SNW could not be explained by variation in dissolution intensity and instead interpreted SNW in terms of local growth conditions. In the Santa Barbara Basin (SBB) prior to 1975, G. bulloides SNWs were highest during times with upwelling of cool waters with lower Ω and showed no external signs of dissolution, suggesting that growth responses to temperature had a greater influence on SNW than carbonate chemistry (Pak et al, 2018).…”
Section: Foraminiferal Shell Weightsmentioning
confidence: 99%
“…For example, lower carbonate ion and pH conditions leads to lower calcification, and thus lower SNW, in at least some species (Bijma et al, 2002;Marshall et al, 2013;Moy et al, 2009). In addition, other aspects of the growth habitat, including temperature, salinity, and food availability, may drive changes in foraminiferal growth and calcification, and thus influence SNW (Beer et al, 2010b;Bijma et al, 1990;Broecker & Clark, 2001;de Villiers, 2004;Pak et al, 2018;Todd et al, 2020;Weinkauf et al, 2016). In some paleoceanographic records, dissolution proxies such as fragmentation counts and external smoothing of shell features show a decoupling between dissolution and SNW (Davis et al, 2016;Pak et al, 2018;Todd et al, 2020 counts as an independent measure of dissolution and found that variation in SNW could not be explained by variation in dissolution intensity and instead interpreted SNW in terms of local growth conditions.…”
Section: Foraminiferal Shell Weightsmentioning
confidence: 99%